Sex-specific associations between the developmental alterations in the pituitary-thyroid hormone axis and thyroid nodules in Chinese euthyroid adults: a community-based cross−sectional study - Li, Ying; Yu, Genfeng; Yao, Nanfang; Liu, Siyang; Wang, Dongmei; Ma, Qintao; Liu, Lan; Wan, Heng; Shen, Jie (Frontiers in Endocrinology, 2024)
Background Previous studies have revealed the sex-specific features of pituitary-thyroid hormone (TH) actions and the prevalence of thyroid nodules (TNs) in children and adolescents.However, it was unclear in adults. We aimed to investigate the features of pituitary-TH actions in women and men at different ages, and the associations of thyrotropin (TSH), THs, and central sensitivity to THs indices including the thyroid feedback quantile-based index by FT4 (TFQIFT4) and the thyroid feedback quantile-based index by FT3(TFQIFT3) with of TNs in Chinese euthyroid adults.Methods 8771 euthyroid adults from the communities in China were involved. Demographic, behavioral, and anthropometric data were gathered through the questionnaires. Ultrasound was performed to evaluate the TNs. TSH and THs levels were measured. The multivariable logistic regression and multivariable ordinal logistic regression were conducted.Results TFQIFT3 among both genders, except women aged 43 to 59 years, where it increased slightly. Additionally, there was an age-related decline in TFQIFT4 levels in both women and men at ages < 50 and < 53, respectively, but a marked increase after that. Lower TSH levels were significantly associated with a higher prevalence and lower odds of having fewer TNs using multiple nodules as the base category in both men and women (both P for trend < 0.05).Additionally, lower TFQIFT3 and TFQIFT4 levels were significantly associated with a higher prevalence of TNs in women (both P for trend < 0.05), and lower TFQIFT3 levels were significantly associated with a higher prevalence of TNs in men. Both higher TFQIFT3 and TFQIFT4 levels were significantly associated with higher odds of having fewer TNs using multiple nodules as the base category in women. However, the relationships between TFQIFT4 and the prevalence or number of TNs in men were not found.The trends of THs, TSH, TFQIFT4, and TFQIFT3 at different ages were sexdependent. Both TFQIFT4 and TFQIFT3 levels were negatively associated with the prevalence and number of TNs in women. The present results may lead to a better understanding of the sex-specific relationships between the development of the pituitary-TH axis and the formation of TNs.